Wireless Solar Charging Systems for Electric Vehicles: Technology, Design, and Implementation Challenges - Arya Shukla; Smita S. Palnitkar; Avdhut Ranaware; Swapnil Gurme (International Journal of Radio Frequency Innovations, 2024)
Higher standards for the ease, safety, and dependability of electric vehicle (EV) charging have been proposed in recent years due to the new energy sector's electrical vehicle (EV) rapid development. Inductive coupling is used for wireless power charging. Both stationary and dynamic situations can be used for inductive coupling. Low energy loss and reduced demands on the primary circuit are achieved by rearranging the transformer and changing the high frequency. The primary circuit can transfer enough battery power to the secondary circuit without causing a significant amount of energy loss. Through the air core transformer, electricity is subsequently transferred to the charging battery, which is electrically connected to the secondary circuit. When buses are waiting at a bus station for shuttle bus services, they can be taxed. It can be applied to rental taxi parking as well. As a result, electric buses only require a small amount of battery charge to reach the next stop. This reduces the size of the battery and encourages electric vehicles to save a lot of money. This technology makes charging stations more efficient by allowing for planned stops and predetermined itineraries, which shortens the charging time. Dynamic charging will encourage the usage of electric cars and cut down on the use of petroleum fuel. With extended charging times and even while the electric car is moving, delays at traffic lights may now be accommodated. Rain and snow are examples of bad weather conditions that have no effect on an electric vehicle's ability to charge.
Keywords: Electric vehicle; Inductive charging; Solar Energy; charging stations; switches; wires